Higher somatic cell counts resulted in higher malondialdehyde concentrations in raw cows' milk - W. Suriyasathaporn (2018)
Lipid peroxidation has been identified as a key factor in numerous pathologies, including inflammation. Therefore, udder inflammation might be related to the quantity of lipid peroxidation in milk. The goal of this study was to identify the relationship between milk somatic cell count (SCC), a marker for inflammatory udder, and malondialdehyde concentration (MDA), a lipid peroxidation marker, in raw cow's milk. Milk samples were collected monthly from each cow in small-holder farms, Mae-On sub-district, Chiang Mai Province, Thailand, from October through December 2004. These samples were used to measure SCC and MDA. To normalize data, SCC values were transformed to somatic cell score (SCS). The data of 161 milk samples of 87 cows from eight farms were used to identify the relationship between SCS and MDA. Statistical analysis showed that SCS was positively related to MDA concentration ( P < 0.0 1). © 2005 Elsevier Ltd. All rights reserved.